Insulin/Insulin-Like Growth Factors in Cancer: New Roles for the Aryl Hydrocarbon Receptor, Tumor Resistance Mechanisms, and New Blocking Strategies - Salisbury, Travis B.; Tomblin, Justin K. (Frontiers in Endocrinology, 2015)
The insulin-like growth factor 1 receptor (IGF1R) and the insulin receptor (IR) are receptor tyrosine kinases (RTKs) that are expressed in cancer cells. The results of different studies indicate that tumor proliferation and survival is dependent on the IGF1R and IR, and that their inhibition leads to reductions in proliferation and increases in cell death. Molecular targeting therapies that have been used in solid tumors include: anti-IGF1R antibodies, anti-IGF1/IGF2 antibodies and small molecule inhibitors that suppress IGF1R and IR kinase activity. New advances in the molecular basis of anti-IGF1R blocking antibodies reveal they are biased agonists and promote the binding of IGF1 to integrin β3 receptors in some cancer cells. Our recent reports indicate that pharmacological aryl hydrocarbon receptor (AHR) ligands inhibit breast cancer cell responses to IGFs, suggesting that targeting AHR may have benefit in cancers whose proliferation and survival are dependent on insulin/IGF signaling. Novel aspects of IGF1R/IR in cancer, such as biased agonism, integrin β3 signaling, AHR and new therapeutic targeting strategies will be discussed.